2015
DOI: 10.1155/2015/573210
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Epithelial Barrier Integrity and Overdrive Activation of Alveolar Epithelial Cells in the Pathogenesis of Acute Respiratory Distress Syndrome and Lung Fibrosis

Abstract: Individual alveolar epithelial cells (AECs) collaboratively form a tight barrier between atmosphere and fluid-filled tissue to enable normal gas exchange. The tight junctions of AECs provide intercellular sealing and are integral to the maintenance of the AEC barrier integrity. Disruption and failure of reconstitution of AEC barrier result in catastrophic consequences, leading to alveolar flooding and subsequent devastating fibrotic scarring. Recent evidences reveal that many of the fibrotic lung diseases invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 92 publications
0
56
0
Order By: Relevance
“…The accelerated senescence of AECs is one of the mechanisms that aggravate the aberrant activation of AECs . Abnormally activated cells activate fibroblasts and myofibroblasts to secrete excess extracellular matrix, leading to the deposition of collagen and destruction of the lung architecture.…”
Section: Resultsmentioning
confidence: 99%
“…The accelerated senescence of AECs is one of the mechanisms that aggravate the aberrant activation of AECs . Abnormally activated cells activate fibroblasts and myofibroblasts to secrete excess extracellular matrix, leading to the deposition of collagen and destruction of the lung architecture.…”
Section: Resultsmentioning
confidence: 99%
“…These findings also highlight the possibility that administration of therapeutic agents that promote barrier protective responses in the developing fetal lung may help alleviate the effects of maternal smoke exposure. Additionally, resident progenitor cell populations may play a role in reestablishing barrier integrity in fetal lungs after injury by tobacco smoke (58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AKT is generally recognized as a key factor in PI3K (phosphatidylinositol 3-kinase) /AKT pathway and acts as a crucial role in cell differentiation, proliferation, metabolism, apoptosis, protein synthesis and transcription [11]. Previous studies have indicated that ARDS can be treated by the inhibition of PI3K/AKT signaling pathway [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%